2016
DOI: 10.1016/j.oceaneng.2016.05.055
|View full text |Cite
|
Sign up to set email alerts
|

An accurate and computationally efficient small-scale nonlinear FEA of flexible risers

Abstract: a b s t r a c tThis paper presents a highly efficient small-scale, detailed finite-element modelling method for flexible risers which can be effectively implemented in a fully-nested (FE 2 ) multiscale analysis based on computational homogenisation. By exploiting cyclic symmetry and applying periodic boundary conditions, only a small fraction of a flexible pipe is used for a detailed nonlinear finite-element analysis at the small scale. In this model, using three-dimensional elements, all layer components are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Fig. 2 Correspondence between a pair of nodes L n and R n on the two end-cross sections and the dummy projected node P n , which is constrained to the reference node P R [11] Fig. 3 Cross section of the SPC Fig.…”
Section: Cross Section and Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 Correspondence between a pair of nodes L n and R n on the two end-cross sections and the dummy projected node P n , which is constrained to the reference node P R [11] Fig. 3 Cross section of the SPC Fig.…”
Section: Cross Section and Materials Propertiesmentioning
confidence: 99%
“…An alternative is to apply the periodic boundary conditions by taking advantage of the helical symmetry of helical wires thanks to the computational homogenization [8]. This method was early developed to tackle the problem for composite structures [9] and are gradually extended to other structures such as helical ropes [10] and flexible pipes [11].…”
Section: Introductionmentioning
confidence: 99%
“…As the key device for transporting hydrocarbon product from sub-sea reservoirs to floating vessels, flexible risers therefore have to withstand huge hydrostatic pressure without collapse. Flexible riser are multilayered tubular structures which consist of helical wound metallic strips and tapes, and extruded polymeric layers (Rahmati et al 2016), as shown in Figure 1 (National Oilwell Varco 2014). The carcass and the pressure armour are two self-interlocking layers wound by metal strips with constant pitches, which take external and internal pressure, separately.…”
Section: Introductionmentioning
confidence: 99%